Pembelajaran Tari Kreatif di RA Nurul Huda Kota Bandung - Vinlandari Wahyudi, Ayu; Gunawan, Indra (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
This study aims to describe creative dance learning at RA Nurul Huda Bandung City. This research uses a qualitative approach with a descriptive analysis method. The subjects of this study were students, school principals, and educator’s RA Nurul Huda, Bandung City. Collecting data by observation, interviews, and documentation. The data analysis used refers to the Milles and Huberman model. While the validity test was done by triangulating techniques and sources. The results of the study can be described that learning creative dance at RA Nurul Huda includes developing themes in the core activities of the learning process. The process of learning creative dance at RA Nurul Huda includes: initial, core and closing activities. The initial activity contains brainstorming, prayers, and reading short letters. This activity contains an explanation of the theme and dancing according to the theme. The closing activity contains evaluation of creative dance activities.